Metalworking fluids (Marcel Dekker, 1994)
The book provides a concise introductory material on metallurgy for the novice, this practical reference presents the state of the art in metalworking fluid technology - detailing its history, formulation, application, maintenance, testing, and government regulation. It covers all important operational aspects of fluids in metalworking. It contains a valuable troubleshooting section on the causes of and cures for common industrial problems related to metalworking fluids, surveys standard laboratory techniques to evaluate the quality and performance of metalworking fluids, examines cutting, grinding, stamping, drwing, and forming operations, analyzes chemical and nonchemical methods to control microorganism in metalworking fluids, summarizes recent studies on how metalworking fluid components affect waste treatment and bioresistance, describes procedures to prolong the use of metalworking fluids and reduce their environmental impact, addresses the skin care and general health concerns of machine operators handling metalworking fluids... The book offers over 425 up-to-date literature citations and more than 225 helpful tables, drawings, equations, photographs, and micrographs